Chemical characterization of an ensiled food for pigs. Technical note - García Hernández, Yaneisy; Sosa, Dailyn; Boucourt, R.; Scull, Idania (Cuban Journal of Agricultural Science, 2016)
To characterize chemically an ensiled, mainly as energetic food, obtained from ensiling sweet potato (Ipomoea batata), Saccharomyces cerevisiae cream, concentrated vinasse and B sugar cane molasses, pH and dry matter percentage (DM), ashes, crude protein (CP) and crude fiber (CF) were determined to food samples, obtained at laboratory scale and in an industrial plant. The silage, produced in both conditions, showed 24.63-33.75 % of DM; 11.27-13.96 % of ashes; 9.66-11.15 % of CP and 3.78-3.61 pH. According to these results, it is considered that sweet potato silage has the appropriate chemical characteristics to be used in the alternative pig feeding.Key words: ensilage, pig food, chemical composition, concentrated vinasse, B molasses.